Численно-полевой анализ электромагнитных процессов в роторе турбогенератора при несимметричной нагрузке - Милых, Владимир Иванович (Інститут електродинаміки НАН України, 2017)
На основе многопозиционных численных расчетов вращающегося магнитного поля проведена оценка работы ротора турбогенератора при его несимметричной нагрузке в рамках ее стандартных ограничений. Результаты расчетов при несимметричной нагрузке, проведенные на примере турбогенератора мощностью 35 МВт, сопоставляются с аналогичными результатами при симметричной нагрузке. Анализируются форма и гармонический состав ЭДС в обмотке ротора и в его пазовых клиньях, делается оценка токов, вызванных этими ЭДС. Рассматриваются также временные функции переменной составляющей магнитной индукции на поверхности вращающегося ротора.

The estimation of the turbo-generator rotor work was conducted under turbo-generator unbalanced loading within the framework of its standard limitations on the basis of the multi-position numerical calculations of the rotating magnetic field. The results of calculations at the asymmetrical loading which were carried out by the example of 35 MW turbogenerator are compared with similar results with symmetrical loading. The form of temporal functions and harmonic composition of the EMF in the rotor winding and in its slot wedges are analyzed, the estimation of currents caused by these EMF is done. Level of the variable EMF in the field winding is very significant, however the variable component of current in it isn't a serious problem. EMF in the rotor wedges reach tens of volts, currents - of the order of 2.5 kA, and in different wedges they differ markedly. The temporal functions of the magnetic induction variable component on the surface of the spinning rotor, whose values increase significantly because of the unbalanced load, are also examined.
The numerically-field analysis of electromagnetic processes in the turbo-generator rotor under unbalanced loading
Keywords: электрические машины; магнитные поля; численные расчеты; ротор; временные функции; turbo-generator; unbalanced loading; magnetic fields; numerical calculations; electromagnetic processes; rotor; temporal functions